Studying an educational intervention and its impact on health-related quality of life and fasting blood glucose levels among patients with type 2 diabetes mellitus in rural China - Shaofan Chen; Kristina Burström; Bo Burström; Dongfu Qian (BMC Health Services Research)
Abstract Background Type 2 diabetes mellitus (T2DM) remains a major public health challenge in rural China, where healthcare access and health literacy are limited. Although primary healthcare (PHC) plays a key role in chronic disease management, evidence on the long-term effects of educational interventions in rural settings is scarce. This study, part of the initiative “Studying the Vertical Integration Strategy of Chronic Disease Service Based on Multiple Incentive Mechanisms in Rural China” (2015–2017), evaluated the impact of a structured educational intervention on fasting blood glucose (FBG) trajectories and health-related quality of life (HRQoL) among rural T2DM patients. Methods A quasi-experimental study was conducted in two rural counties in Jiangsu Province, enrolling 784 patients (389 intervention, 395 control) from township health center registries. Over 24 months, the intervention group received bi-monthly education sessions, home visits, and enhanced provider training, while the control group received routine care. Outcomes were measured at baseline (2015) and two follow-ups (2016, 2017). FBG levels and HRQoL (assessed via EQ-5D-3 L, EQ-VAS, and Paretian Classification of Health Change [PCHC]) were analyzed using difference-in-differences (DID) models and multinomial logistic regression. Results After adjusted for potential confounding factors, the intervention group exhibited a slower FBG increase compared to controls (DID: -0.65, 95% CI: -1.13 to -0.17), despite an overall upward trend in both groups. HRQoL improvements were significant in the intervention group, with greater gains in mobility (84.7% vs. 86.0% reporting “no problems” in 2017, p < 0.001), pain/discomfort (62.3% vs. 55.4%, p < 0.001), and anxiety reduction (80.7% vs. 78.5%, p < 0.001). The PCHC analysis revealed intervention participants were 1.83 times more likely to improve (95% CI: 1.29–2.59) and had 83% lower risk of deterioration (OR: 0.17, 95% CI: 0.09–0.34) versus controls. Conclusion Structured educational interventions embedded in rural PHC systems effectively attenuated glycemic deterioration and enhanced multidimensional well-being in T2DM patients. However, continued FBG elevation signals the need for more comprehensive strategies, integrating digital tools and workforce reforms. Trial registration ISRCTN13319989 (Date: 31/07/2019).